KONSEP KEUNTUNGAN DALAM SYIRKAH AL-INAN DAN APLIKASINYA PADA BANK SYARIAH DI INDONESIA - Ahmad Syarbaini (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2026)
Islamic banking like other conventional banks, functions as an intermediary institution, meaning it is able to collect and distribute funds from various economic units to other economic units in need. Fund distribution by Islamic banking can be done in the form of funding based on the principle of profit and loss and profit sharing (PLS), namely mudharabah and musyarakah. Musyarakah is the best funding under Islamic law because this type of funding is based on the participation of the bank and consumers in capital investment, profit sharing, and responsibility for losses or risks arising from certain projects. The purpose and intent of this study is to analyze and describe the implementation of the Sharia system in Islamic banks in Indonesia, where Bank Sharia Indonesia, does not practice sharia principle in their entirety